A comprehensive data-based assessment of forest ecosystem carbon stocks in the US 1907–2012. (19th December 2019) - Magerl, Andreas; Le Noë, Julia; Erb, Karl-Heinz; Bhan, Manan; Gingrich, Simone
Abstract: The consistent and robust assessment of ecosystem carbon stocks remains central to developing and monitoring climate change mitigation strategies. Here, we investigate the dynamics of forest ecosystem carbon stocks in the conterminous United States between 1907 and 2012 at national and regional levels. We build upon timber volume records from historical forest inventories and use a modelling approach to include all relevant pools, e.g. soil carbon, to derive a comprehensive long-term dataset. We find a consistent increase in forest carbon stocks across the country, from 27 PgC in 1907 to 39 PgC in 2012, with persistent regional variations between western and eastern United States, signalling pronounced land use and land management legacy effects. We identify additional potential to increase forest C sinks in both west and east, on diverging levels. Extended forest C stocks stem from forest biomass thickening i.e. increases in biomass C densities, rather than forest area expansion. Our study reflects the first such effort to collectively understand the effects of environmental change and land management on contemporary biomass C stocks at the national level, and critically engages with ongoing initiatives towards assessing the potential for carbon sequestration in forest ecosystems.